Eligible patients with heart failure prescribed vs. not prescribed vericiguat in the United States - Greene, Stephen J.; Coyle, Catelyn R.; Hancock, Lucy N.; Tebbs, Kathryn W.; Barlow, Sophie G.; Stevenson, Andra S.; Obi, Engels N. (Frontiers in Cardiovascular Medicine, 2025)
AimsThis study compared characteristics of patients with heart failure (HF) prescribed vericiguat vs. eligible patients with HF not prescribed vericiguat, and sought to identify factors associated with vericiguat use in real-world settings.MethodsWe analysed 2022–2023 Adelphi HF cross-sectional survey from United States physicians and their adult patients. Patients prescribed vericiguat were compared with patients eligible for but not prescribed vericiguat. Vericiguat eligibility was defined as ≥1 prior HF hospitalization at any time, ejection fraction (EF) <45%, and no stage 5 chronic kidney disease or need for dialysis. Both cohorts were compared descriptively, and logistic regression used to identify factors associated with vericiguat non-use.ResultsOverall, 93 physicians reported data on 228 patients with HF (mean age [SD]: 66.8 years [11.8], 65.7% male, 60.1% White), with 98 patients prescribed vericiguat and 130 patients eligible but not prescribed vericiguat. Patients eligible but not prescribed vericiguat had more comorbid hypertension (62.3% vs. 45.9%), hyperlipidemia (52.3% vs. 34.7%), and lower EF (mean [SD]: 34.7% [5.8%] vs. 41.7% [9.6%]), all p < 0.05. For every 1% increase in EF above 38%, odds of being prescribed vericiguat increased by 44% (Odds Ratio [CI]: 1.44 [1.28, 1.63]; p < 0.05).ConclusionAmong patients with HF in contemporary US clinical practice, patients prescribed vericiguat have distinct demographic and clinical profiles compared to eligible patients not prescribed vericiguat. Future research should confirm these findings and explore whether subgroups of eligible patients less likely to be prescribed vericiguat may benefit from targeted implementation initiatives.